Discrete hall sensor based vector control algorithm of permanent magnet synchronous motor - Korobatov, D. V.; Kulmukhametova, A. S. (2015 International Siberian Conference on Control and Communications (SIBCON), 2015)
New vector control algorithm of permanent magnet synchronous motor is proposed. Algorithm varies from its counterparts by simplicity and robustness.